Development of Physics Mobile Learning Based on Local Wisdom to Improve Vector and Diagram Representation Abilities - Husna, Miftahul; Kuswanto, Heru (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The research aims to 1) develop a feasible physics learning media based on local wisdom (waterwheel); 2) measure the improvement of student’s representation abilities after using of learning media based on local wisdom . The development of media used 4D model ; (a) define, (b) develop, (c) design, and (d) disseminate. The feasibility of the learning media is obtained through expert validation and limited test. The improvement of the students’ vector representation and diagram representation abilities was obtained through field test.The participants of field test were 25 students of experimental class and 25 students of control class in SMAN 3 Yogyakarta. The results show that the local wisdom-based learning media is feasible to use based on the expert validation and limited test. The gain score obtained from field test showed that that the learning media can improve the students’ vector representation and diagram representation abilities.